PENGARUH PEMAHAMAN WAJIB PAJAK, KESADARAN WAJIB PAJAK DAN PERILAKU WAJIB PAJAK TERHADAP KEPATUHAN PERPAJAKAN E-COMMERCE - Fauzi, Fauzi; Hasnarika, Hasnarika; Annisa Nur Fadila; Afriyadi, Afriyadi (Juremi: Jurnal Riset Ekonomi, 2024)
This study aims to determine the influence of how much taxpayer understanding, taxpayer awareness and taxpayer behavior have on e-commerce tax compliance. This study used a sample of 51 respondents using a non-probability sampling technique, namely census or total sampling. The method used in this study is a quantitative method. The object of this research is the e-commerce shoppee business actor in the city of Tanjungpinang. Data collection was carried out using two methods, namely questionnaires and literature study. Where respondents filled out a questionnaire of 24 statement items related to the variable being measured. The data analysis technique used is the Jeffrey's Amazing Statistics Program (JASP) application version 0.16. The results of this study indicate that there is a significant influence between taxpayer understanding (X1), taxpayer awareness (X2) and taxpayer behavior (X3) on e-commerce taxpayer compliance (Y).